Design and development of mobile learning module for self-directed learning to enhance english for academic survival skills - Md. Ngadiran, Nurizah (2020)
This research design and development research (DDR) was done to develop mobile learning (mLearning) module for self-directed learning (SDL) to enhance English for academic survival skills (Tutor Me). ‘Tutor Me’ was developed to assist lowproficiency ESL learners who enrol in UHB 10302 course (English for Academic Survival) in UTHM to develop their English for academic survival skills, which include effective reading, effective listening, paragraph writing and presentation skills. It is crucial for the targeted students to be assisted with a comprehensive module to be used during tutorial sessions and Independent Study Hours (ISH) sessions. The research objectives for Phase One (Needs Analysis) are to identify relevant theories and empirical studies to construct the mLearning module design principles, and to examine the needs among the lecturers and the students for the mLearning module. 10 lecturers and 74 students were involved in this phase. As for Phase Two (Design and Development), the objectives are to construct the mLearning module design principles, and to develop ‘Tutor Me’ based on the feedback from the panel of experts that should be in-line with the students’ and lecturers’ feedback gathered in Phase One. Five of the experts were in the field of ‘English for Academic Survival’, and another five experts were in the field of ‘Technology in Education’. The objectives of Phase Three (Evaluation) are to evaluate the users’ viewpoints of ‘Tutor Me’ and to examine the students’ pre- and post-tests scores. In this phase, 48 students were involved, whereby 24 students took the course during Semester 2, Session 2018/2019, while another 24 students were from Special Semester, Session 2019/2020. Amongst the primary findings of Phase One is learning management system (LMS) should be the operational platform for the mLearning module. The platform should be made accessible using smartphones and laptops for SDL to assist them in improving their English for academic survival skills. Based on the feedback given by the students, lecturers and panel of experts through survey questions, in Phase Two ‘Tutor Me’ was developed, incorporating elements such as content, learning strategies, learning activities, media and assessments. Following that, ‘Tutor Me’ underwent the process of content validity and reliability. For the findings of Phase Three, through the feedback gathered from the interview questions and post-test writing essays, the lecturer and students were satisfied with the ability of ‘Tutor Me’ to be accessed for SDL regardless of place and time, which can the students in improving their English for academic survival skills. Referring to the paired-samples t-test analysis of the pre- and post-tests scores, the pvalue achieved for effective reading skills, effective listening skills, paragraph writing skills and presentation skills is less than α=0.05. Hence, it can be summarised that ‘Tutor Me’ is successful in improving the students’ English for academic survival skills. The implication of this study focuses on the development of the mLearning module for SDL to enhance the students’ English for academic survival skills, the procedure to conduct a research on module design and development, and further suggestions for the Ministry of Higher Education, UTHM, the lecturers and students, and the field of English language teaching (ELT).